Die europäische Rechtsgemeinschaft vor den Herausforderungen von Vertiefung und Erweiterung. Vortrag auf dem Kölner Symposium "50 Jahre Römische Verträge" am 13. April 2007 - Danwitz, Thomas von (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2010)
With regard to the further deepening of European integration as well as further enlargement of the Community, skepticism is the predominant response among European citizens at the moment. The citizens want to be convinced by the European institutions. The realization of publicly-announced goals and the tackling of social problems could achieve this. In the context of the enlargement process, adequate treatment of the different preconditions and values in the member states and the functioning of the Community institutions are essential. The Court of Justice can make a convincing contribution. At present, it has to uphold the claim of supranationality during the integration process and must respond to fundamental questions regarding personal liberty and an effective fight against terrorism. Its everyday judgments deal mainly with measures to complete the internal market. Some concrete developments in the area of liberalization of services in telecommunications and other sectors, of tax law and of the law relating to the posting of workers will be described. The integration measures to realize the area of freedom, security and justice are another subject of current case law, in particular problems regarding the mutual recognition of legal norms. In addition, questions relating to competencies and forms of action after the Treaty of the European Union are of great institutional importance. Not least to preserve the acceptance of its adjudication, the Court of Justice must pursue and further shape the protection of the identity and sovereignty of the member states alongside furthering integration.